KAJIAN TERHADAP PENGATURAN PRINSIP TRANSFER OF UNDERTAKING PROTECTION OF EMPLOYMENT (TUPE) SEBAGAI UPAYA PERLINDUNGAN HUKUM TERHADAP PEKERJA DALAM PELAKSANAAN OUTSOURCING BERDASARKAN PERJANJIAN KERJA WAKTU TERTENTU (PKWT) - , KD AGUS SUDIARAWAN, Dr. Ari Hernawan, S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is aimed identifying the advantages of the regulation of TUPE principles, synchronization of the regulation of the requirements of Partial Work Transfer to Other Companies in the Regulation of Minister of Manpower and Transmigration of the Republic of Indonesia Number 19 of 2012 and the Circular Letter Minister of Manpower and Transmigration of the Republic of Indonesia Number 04 / MEN /VIII/2013 in response to the Decision of the Constitutional Court Number 27/PUU-IX/ 2011, as well as inhibiting factors for outsourcing companies to apply the TUPE principles after the Decision of the Constitutional Court. The research was conducted by using normative-empirical method. The data of the research consisted of primary data and secondary data. All of the collected data were analyzed using qualitative method. The results of this research were presented in a descriptive analysis report. The results of the research indicated he advantages that could be obtained by workers in relation with regulation of the TUPE principles included protection of wages, welfare and working requirements, protection of workers when the company was taken over, protection of workers when there is a change of outsourcing company and regulation of the right to file a lawsuit to the industrial relations court. In regard to the synchronization, there were several provisions in the Regulation of Minister of Manpower and Transmigration and the Circular Letter of Minister of Manpower and Transmigration such as the regulation of procedures and requirements of work transfer to other companies, authority of business sector associations, mechanism of company registration, regulation of severance and sanctions which substantially did not synchronize with and tended to weaken the spirit of the TUPE principles in the Decision of Constitutional Court. The inhibiting factors in the application of the TUPE principles in the outsourcing companies after the Decision of Constitutional Court were the lack of socialization and supervision of the government, various legal loopholes of discrepancies between the implementing regulation and the Decision of Constitutional Court, uncertainty severance regulation, assumptions that TUPE was a new burden which may disadvantage employers, and the lack of understanding of the workers related to their rights. Key words: TUPE, Legal Protection, Outsourcing, FTEC